Pengaruh Pemberian Edukasi Menggunakan Video dengan Self Stigma dan Kepatuhan Minum Arv Pada ODHA di Klinik VCT Marjorie - Simson Fermande Tameon; Ni Luh Widani; Wilhelmus Hary Susilo (Universitas Pahlawan Tuanku Tambusai, 2025)
HIV weakens the immune system. ARV medication is effective if taken consistently, but non-adherence can lead to virus resistance and high transmission risk. This study aims to analyze the impact of video education on self-stigma and ARV medication adherence among people living with HIV (PLHIV). Using a quasi-experimental design with a pre-test and post-test control group, the study involved 68 respondents (34 intervention, 34 control) selected through purposive sampling at the Marjorie VCT Clinic from July to August 2023. The intervention consisted of a 4-week educational video. Most respondents were aged 36-45 years (47.1%), female (52.9%), had secondary education (60.3%), were employed (57.4%), and had been on treatment for 1-5 years (55.9%). The intervention group showed increased adherence and reduced self-stigma. The Wilcoxon test indicated significant differences in adherence and self-stigma after the intervention, with p-values of 0.000 (<0.05). The Mann-Whitney test revealed significant differences between the intervention and control groups in medication adherence and self-stigma, with p-values of 0.007 and 0.023. The Ordinal Logistic Regression test showed no significant effect of age, gender, and education on medication adherence and self-stigma, with p-values of 0.042 and 0.998. The educational video contributed 34.1% to medication adherence and 34.3% to self-stigma reduction. This study recommends using educational videos as an intervention by nurses to enhance medication adherence and reduce self-stigma.